Advertising Procedure / Thirteenth Edition - Lane Ronald W; Russell Thomas J (Prentice Hall, 1996)
Preface, Acknowledgements, The Place of Advertising, Planning the Advertising, Managing the Advertising, Media, Creating the Advertising, Other Environments of Advertising, Index.
Preface, Acknowledgements, The Place of Advertising, Planning the Advertising, Managing the Advertising, Media, Creating the Advertising, Other Environments of Advertising, Index.